1997
DOI: 10.1259/bjr.70.834.9227250
|View full text |Cite
|
Sign up to set email alerts
|

Male and female normative data for ultrasound measurement of the calcaneus within the UK adult population.

Abstract: The establishment of accurate normative data for specific populations is required before ultrasound bone densitometry may be considered for routine clinical application. A single general practice was utilized, representing both rural and urban populations, to recruit 169 male and 210 female subjects in the age range 20-80 years. Measurements of broadband ultrasound attenuation (BUA) and velocity (VOS) of the left calcaneus were undertaken using the McCue CUBAClinical II system. Two descriptive statistical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 13 publications
5
15
0
2
Order By: Relevance
“…Mean DXA measurements (shown in Table 2) are comparable with previous published data using the Hologic QDR-1000 machine [39,40]. QUS measurements are comparable to previous published data using the same equipment in the UK [41] (Table 3).…”
Section: Resultssupporting
confidence: 87%
“…Mean DXA measurements (shown in Table 2) are comparable with previous published data using the Hologic QDR-1000 machine [39,40]. QUS measurements are comparable to previous published data using the same equipment in the UK [41] (Table 3).…”
Section: Resultssupporting
confidence: 87%
“…At all measurement sites SOS initially increases and peaks between the third and fourth decade of life. This is in accordance with previous studies indicating that QUS properties reach peakvalues at an older age [13] than the DXA-determined BMD [14]. This discrepancy argues that QUS-measured bone properties are different from those evaluated by DXA, and mature at later stages of life.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in elderly women have identified age, body composition and physical activity as determinants of QUS parameters [15,16], but there have been few studies of QUS in men, or indeed elderly men. One study compared QUS in 169 normal men and 210 normal women aged 20-80 years [17]. BUA was higher in men than women at all ages but showed little decline in either sex after age 60 years.…”
Section: Discussionmentioning
confidence: 99%